2010
DOI: 10.1007/s00497-010-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

Early germination of Arabidopsis pollen in a double null mutant for the arabinogalactan protein genes AGP6 and AGP11

Abstract: The pollen specificity of the Arabidopsis arabinogalactan protein (AGP) genes AGP6 and AGP11 suggests that they are integral to pollen biogenesis, and their high percent of sequence similarity may indicate a potential for overlapping function. Arabidopsis agp6 agp11 double null mutants have been studied in our laboratory, and in the present work, we characterize the germination and growth of its pollen. When compared to wild type, mutant agp6 agp11 pollen displayed reduced germination and elongation, both in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 23 publications
0
61
0
1
Order By: Relevance
“…For the 16 Arabidopsis GPI-AGPs, there are some robust groupings (greater than 70% bootstrap values), but only between pairs of sequences. For example, the pollen-specific AtAGP6 and AtAGP11 (Pereira et al, 2006;Coimbra et al, 2009Coimbra et al, , 2010 A, Protein disorder (PONDR) plots (see "Materials and Methods") for AtAGP6 (At5g14380; left), AtEXT3 (At1g21310; middle), and prolyl-4-hydroxylase (AtP4H1; At2g43080; right) using VL-XT (red), VL3 (green), and VSL2 (blue). PONDR prediction scores above the threshold line (0.5) predict disorder; below the line, they predict order.…”
Section: Resultsmentioning
confidence: 99%
“…For the 16 Arabidopsis GPI-AGPs, there are some robust groupings (greater than 70% bootstrap values), but only between pairs of sequences. For example, the pollen-specific AtAGP6 and AtAGP11 (Pereira et al, 2006;Coimbra et al, 2009Coimbra et al, , 2010 A, Protein disorder (PONDR) plots (see "Materials and Methods") for AtAGP6 (At5g14380; left), AtEXT3 (At1g21310; middle), and prolyl-4-hydroxylase (AtP4H1; At2g43080; right) using VL-XT (red), VL3 (green), and VSL2 (blue). PONDR prediction scores above the threshold line (0.5) predict disorder; below the line, they predict order.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies aiming at a more inclusive phenotypic characterization of the agp6 agp11 double null mutants, it was detected that a number of pollen grains germinated precociously inside the anthers and this phenomenon was dependent upon the relative humidity of the growth chamber (Coimbra et al, 2010). Pollen germination inside anthers was not observed in single agp6 or agp11 mutants, and therefore those observations indicated that the double mutation was needed to induce the precocious germination character.…”
Section: Reverse Geneticsmentioning
confidence: 95%
“…We have further characterized the anthers and pollen of agp6 agp11 and concluded that both AGPs, AGP6 and AGP11, are necessary for the proper pollen tube growth as well as for preventing untimely pollen grain germination (Coimbra et al, 2010). Further details on the biology of pollen-specific AGPs are expected to emerge from a microarray experiment performed on RNA isolated from pollen tubes of agp6 agp11 mutant, and which is currently under analysis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…A few AGPs, for example, AtAGP6 and AtAGP11, have been implicated in pollen development (Coimbra et al, 2009). A double null agp6 agp11 mutant has collapsed pollen grains, reduced (and precocious) pollen grain germination and tube elongation, and displays shorter fruits with less seeds; these phenotypes are due to pollen abortion (Coimbra et al, 2009(Coimbra et al, , 2010.BLAST searches of the Arabidopsis genome using mammalian b-(1,3)-GalT sequences as queries identified 20 genes of the CAZy Glycosyltransferase (GT) 31 family (www.cazy.org/) as potentially being involved in the synthesis of the type II AG backbone of AGPs (Qu et al, 2008). Based on phylogenetic analysis, the Arabidopsis GT31 family GalTs were grouped into four clades [clades 1 (VIII and IX), 7 (V and VI), 10 (I to IV), and 11 (VII); Qu et al, 2008;Egelund et al, 2011].…”
mentioning
confidence: 99%